Enhancing Photoacoustic Intensity of Upconversion Nanoparticles by Photoswitchable Azobenzene‐Containing Polymers for Dual NIR‐II and Photoacoustic Imaging In Vivo. Issue 12 (16th April 2019) - He, Shuqing; Song, Jun; Liu, Jianfeng; Liu, Liwei; Qu, Junle; Cheng, Zhen
Abstract: Near‐infrared photoacoustic (PA) imaging is developing rapidly as an alternative to optical imaging and promises benefits in terms of deeper tissue penetration and higher spatial resolution. This paper proposes a strategy to enhance the PA intensity of upconverted nanoparticles (UCNPs) by functionalized photoswitchable azobenzene‐containing poly (acrylic acid) (UCNPs@PAA‐Azo) to yield a PA signal that is up to six times higher than that of UCNPs without a decay in NIR‐II emission. The mechanism of enhanced photoacoustic activity of the UCNPs@PAA‐Azo can be attributed to the decay of UV and blue light as well as vibrations of the azobenzene group. This technology delivers high resolution of the hind limb vasculature using dual NIR‐II and PA imaging. Using this nanoprobe, NIR‐II imaging provides real‐time means for the precise resection of the lymph node (LN) during surgery, where PA imaging allows for quicker (up to 30 min) detection of LNs than that through NIR‐II imaging. Combining the advantages of dual NIR‐II and PA modalities allows us to achieve complementary information and improve the accuracy of disease diagnosis. This work is critical to the synthesis of dual NIR‐II and PA modal probes and is utilized in small animals imaging with high resolution and a high signal‐to‐noise ratio. Abstract : Photoswitchable azobenzene‐containing photoisomerization polymer (PAA‐Azo) functionalizes upconversion nanoparticles to combine photoacoustic and NIR‐II dual model imaging together to acquire complementary information and synergistically enhance the efficacy in diagnosis and in guided surgery.